SIMULACRUM MEDIA DI ERA POSTMODERN: Analisa Semiotika Jean Baudrillard dalam Narasi Iklan Kecantikan Dove Edisi ‘Dove Real Beauty Sketches’ - Rizqi Fitrianti (Gapenas Publisher, 2021)
Female beauty has become a mass media commodity, so many women are exploited in ad impressions. As a result, women are often positioned as sign objects, not as subjects. In this postmodern era, where everything is no longer a single meaning, hyperreality in mass media becomes a commonplace. The problem raised to be the object of research in this study is a form of simulation by media actors in delivering messages and information in Dove ads ‘Dove Real Beauty Sketches’, thus becoming a hyperrealist show. This study aims to determine the simulation of language used by the media, and to know the extent to which hyperrealist that occurs can form the mindset of the audience into what is formed by the media. The method used in this research using semiotic analysis qualitatively. Data collection conducted by library study and narrative analysis using Jean Baudrillard simulation theory. From the research results obtained conclusion as follows: First, the simulation in the ad impressions is done in many forms, not only through language but also through high technology applications. The simulation has led the audience's mindset that the ads are real. Second, hyperrealist that occurs due to the simulation process that made the ad into the consumption of banalities which in the end still sell the product, not give the beauty education as the ad is conveyed